Synthesis of graphene quantum dots-coated hierarchical CuO microspheres composite for use as binder-free anode for lithium-ion batteries. (1st October 2021) - Kim, Jongmin; Jang, Wooree; Kim, Ji Hoon; Yang, Cheol-Min
Abstract: There is an urgent need to develop improved anode materials for lithium-ion batteries (LIBs). Herein, we report the synthesis of a graphene quantum dots (GQDs)-coated hierarchical nanoflake-based CuO microspheres ( H –CuO) composite on Cu foam via a one-pot hydrothermal technique for use as a binder-free anode for LIBs. The carboxyl-functionalized GQD coating on H –CuO not only results in lower charge-transfer resistance and enhanced electrical conductivity but also prevents the dissolution and agglomeration of the electrode. The GQDs/ H –CuO composite anode exhibits a reversible capacity as high as 609 mAh g −1 (pristine H –CuO: 61 mAh g −1 ) after 200 cycles at 0.2 A g −1 . It also shows long-term cycling stability, exhibiting a capacity retention rate of 79.4% after 1000 cycles (pristine H –CuO: 0.7%) at a high current density (2 A g −1 ) and improved initial coulombic efficiency at 88.2% (pristine H –CuO: 75.2%). The superior electrochemical properties of the GQDs/ H –CuO composite anode are attributable to the graphene networks, which help maintain a high specific surface area and effectively protect the anodic active material from forming an unstable solid electrolyte interface layer. The proposed strategy for fabricating the GQD-coated metal oxide microsphere-based anode should contribute to the development of next-generation LIBs with improved electrochemical performance. Graphical abstract: Image 1 Highlights: Graphene quantum dots (GQDs)/hierarchical CuO microspheres ( H -CuO) composite is fabricated via hydrothermal technique. The GQDs/ H –CuO composite is used as a binder-free anode for lithium-ion batteries. The GQDs/ H –CuO composite anode exhibits high reversible capacity. The GQDs/ H –CuO composite anode exhibits excellent long-term cycling stability.